The importance of using the expertise as a tool to aid in the resolutions of procedural claims in the judicial scope. (Reflection and Critique Law Magazine, 2024)
This study reflects the importance of judicial expertise. It investigated the following problem: "Does the Judicial Expertise assist the operators of the Law in their decisions?". It cogitated the following hypothesis: "the expert practice supplies the needs of magistrates". The general objective is "to analyze the benefit of experts in the sentencing act". The specific objectives are: "to conceptualize the expert's profession", "to list the types of expert reports required in court", and "to describe their objectives". This work is important for the operators of Law because it clarifies the relevance of the expert as a judicial assistant; for science, it demonstrates the formalities followed by Experts; it adds to society because it shows that the expert's job culminates in the full exercise of citizens' rights. This is a six-month qualitative theoretical research project.